State of Governance, Development and Diplomacy in Republic Nepal - Shrestha, Rajendra B. (NCWA Annual Journal, 2024)
A new constitution was promulgated in 2015. There are several major problems in the execution of the constitution in achieving the aspired goals. It excludes the participation of large sections of society. All three branches of government, the executive, legislative and judiciary, lack coordination, autonomy, and effectiveness in carrying out their respective duties. They are marred by corruption, nepotism, and non-adherence to the rules, norms and values that govern them. The economy is in shambles with all the key economic indicators showing negative trends. The economy, development works and delivery of basic needs/services are in dire need of major improvement. Over the years, development strategy and priority have prevented the economy from being self-reliant and sustainable. Nepal’s foreign policy execution in recent years has become more and more unbalanced and ineffective threatening its autonomy, independence, sovereignty and non-aligned policy. The need of the day is a system that promotes unity and inclusiveness of all sections of society.